Influence of Teachers Years of Teaching Experience on their Teaching Approaches in Secondary School, Ilorin Metropolis, Kwara State (Faculty of Social Science, Universitas Negeri Semarang, 2022)
This study investigated the influence of teachers’ years of teaching experience on their teaching approaches in secondary school in Ilorin Metropolis, Kwara State. The population for this study comprised all teachers in secondary schools (Upper basic and senior school) in the Ilorin metropolis. A researcher-designed questionnaire with psychometric properties of content validity and reliability index of 0.84 was used to elicit the needed data. Descriptive statistics of frequency count, percentage and mean. Findings revealed that teachers years of experience influences their teaching approach such as pay little and limited attention to the teaching process which include using teaching aids, adequate and up to date lesson plans, use of a learning management system for teaching and evaluation among others. It was recommended that teachers Teachers should be encouraged to constantly update their notes and be encourage to always write lesson note for the teaching of different subjects. This become imperative because education and society are dynamic, so teaching and learning must be ready to be inline with the dynamic nature of the society among others.